Diskursus Modernisme dalam Pendidikan Islam Perspektif Filsafat Nilai - Mahyudin, Edy; Abdurrahmansyah, Abdurrahmansyah; Sirozi, M.; Hasan, Muflikhul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the Discourse of Modernism in Islamic Education from the Perspective of the Philosophy of Values. The type of research used is library research, which involves analyzing various conceptual information and data, both qualitative and quantitative, derived from previous scholarly articles. The data analysis techniques in this library research include data reduction, categorization, thematic synthesis, interpretation, and theoretical conclusion drawing. Based on the findings and discussion, the discourse of modernism in Islamic education from the perspective of the philosophy of values emphasizes the importance of harmonizing Islamic teachings with the development of modern science and technology in a selective manner. Modernism is not understood as blind acceptance of new ideas, but as a filtering process to ensure alignment with Islamic principles. Islamic education is required to integrate religious and general knowledge in order to produce a generation that is both Islamic in character and globally competitive. Value-related challenges arise from spiritual crises, materialism, and the negative impacts of technology. Therefore, the philosophy of values serves as a reconstructive approach to balance knowledge, faith, morality, and social responsibility in order to form insan kamil with an authentic Islamic identity.